Features of electron beam evaporation under surface electron beam formation - Mysiura, I.N.; Girka, I.A.; Azarenkov, N.A.; Borgun, Ie.V.; Hrechko, Ya.O.; Hryhorenko, A.V.; Dimitrova, V.D.; Ryabchikov, D.L.; Sereda, I.N.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2014)
In this paper, the features of the dense plasma generation under the thermal substance evaporation by an electron beam, formed directly at the crucible surface, have been investigated. Peculiarities of the research are the following: the initial plasma is used as the electron emitter and the electron acceleration occurs in the layer between the initial and thermionic plasma. It has been shown that in the case of the thermionic plasma formation, the crucible current can be several times higher than the discharge current of the primary plasma source due to the redistribution of voltge drop (100…200 V) from the crucible to the wall.